Older Adults' Emotional Challenges and Co-design Preferences for a Social Robot after the COVID-19 Pandemic - Muneeb Ahmad
Mental health challenges became more prevalent during the COVID-19 pandemic, especially among older adults. Consequently, we witnessed an uptake of new technologies, including social robots to address these challenges. However, we observed limited inclusion of older adults in the design process to design these technologies to cater user needs during the pandemic. To address this gap, we conducted a co-design workshop with 17 older adults and explored their emotional challenges after the COVID-19 pandemic. They evaluated the current social robot designs available in the literature and elicited the design preferences for a social robot to address their current emotional challenges. Our results based on thematic analysis show that the impact of the pandemic on older adults' emotional challenges is persisting, and the companionship of a social robot is preferred to enhance their mental well-being. We also show that older adults preferred an animal-like robot design embodied with soft skin possessing a medium size. These findings highlighted older adults' design choices of a social robot and affirmed their potential to support older adults' mental well-being.